América Latina luego del mito del progreso neoliberal: las políticas sociales y el problema de la desigualdad - Claudia C. Danani (Ciências Sociais Unisinos)
The article develops three sections: the first focuses on the theoretical and political differences between equality and equity and also analyzes why equity replaced equality during period of Neoliberal hegemony. In the second section process of individuation and communitation into social policies are analyzed, especially at Neoliberal process of reform. Finally, a brief discussion on the need of rescue the citizenship into Public Education and Public Health is developed in the third section. In this last section the author also argues that a progressive new process requires new social and labor practices from public agents in order to ally to institutions clients.